Prevalence of Anxiety and Burnout in Paramedics and Security Workers during COVID-19 - Muhammad Abdullah, Nasreen Akhtar, Iqra Ameer, Ahmad Altaf, Faiza Liaqat, (Pakistan Journal of Medical & Health Sciences, 2022)
Corona Virus disease has been proved a global health risk and put an extraordinary effect on paramedics and security workers around the world. Our aim is to explore the prevalence of burnout and anxiety among paramedics and security workers during COVID-19 era through quantitative research method. The level of burnout, and anxiety were measured by Oldenburg burnout inventory and Zung self-rating anxiety scale, respectively .We found that 21% of sample was affected by anxiety, 48% faced high level burnout whereas 40 % faced medium level burnout. There was also positive relationship between anxiety and burnout as p value was less than 0.05. This epidemic can cause anxiety and stress in healthcare workers, which can in turn give rise to multiple mental health issues like burnout, anxiety and depression. Precautionary measures as well as early diagnosis and coping strategies can play vital role during this pandemic time frame.